PENGEMBANGAN MEDIA PEMBELAJARAN POWERPOINT INTERAKTIF BERBASIS PENDEKATAN SAINTIFIK PADA PEMBELAJARAN IPA SISWA KELAS IV - Aslina Afi Saputri; lia Nur Atiqoh Bela Dina; Zuhkhriyan Zakaria (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The development research aims to develop interactive powerpoint learning media based on a scientific approach in science learning for fourth grade students. This study uses the Research and Development (RnD) method with the ADDIE development model according to Lee & Owens which consists of five stages, namely analysis, design, development, implementation and evaluation. Sampling using validation techniques from design experts and material experts. The result of the development of interactive powerpoint media, especially the style material that has been developed by researchers according to design experts and material experts. Design experts get a percentage of 80% which is a feasible category to use. Meanwhile, material experts have a percentage of 86,6% which is included in the very feasible category to use. The recapitulation result from the two experts obtained an average of 83,3% with a very decent category. Student responses at the time of product testing obtained a percentage of 93,6% with a very decent category. The result of this study indicate that the interactive powerpoint learning media based on a scientific approach in science learning for fourth grade students that has been developed by researchers is very feasible and can be used interactive media in learning activities. Keywords: Interactive powerpoint media,scientific approach,  science learning.